Family and childhood issues in the 1940s and 1960s, and their reflection on the pages of the periodical press of the Rostov region - M. A. Ponomareva; A. S. Ruman (Гуманитарные и юридические исследования)
Introduction. The article is devoted to the study of individual measures of the Soviet government within the framework of the social policy of the USSR aimed at improving the living conditions of families, their material well-being and increasing the birth rate of the population in the Rostov region.Materials and methods. Special attention is paid to the materials of the periodical press of the Rostov region of 1940-1970, on the pages of which the problems of raising children and youth were reflected, moral themes were highlighted, negative images of irresponsible parents were criticized. The regional newspapers made it possible to conduct a comparative historical analysis of trends and contradictions between the policy of the CPSU and the government carried out “from above” and its perception in society, especially among women.Analysis. The article emphasizes the importance of publications in newspapers and magazines devoted to the topic of “single mothers” and their children who have a dash in the column “father” in the metric certificate. It is noted that, despite the seriousness of the problem that needs to be solved, declared by the society, it remained without attention from the authorities.Results. It is concluded that the periodical press was aimed at the broad strata of the population and promoted family values, formed the image of the ideal Soviet family. In addition, it is emphasized that the tone and vector of publications set the direction for the steady formation of a positive image of a Soviet woman, mother, worker in the reader.